Incidence and Risk Factors of Surgical Site Infection in 376 Mastectomy Procedures in Female Dogs: A Retrospective Cohort Study - Manuel Fuertes-Recuero; Silvia Penelo; María Suarez-Redondo; Alba Eceiza-Zubicaray; Mario Arenillas; Guillermo Valdivia; Paula García San José; Laura Peña; Dolores Pérez-Alenza; Gustavo Ortiz-Díez (Veterinary Sciences, 2025)
The incidence of surgical site infection (SSI) following mastectomy in female dogs remains poorly characterized, despite its relevance to postoperative outcomes and patient welfare. This retrospective cohort study aimed to determine the incidence of SSI and identify associated clinical and surgical risk factors in dogs undergoing mastectomy procedures at a veterinary teaching hospital between 2013 and 2022. SSI diagnosis was based on the Centers for Disease Control (CDC) criteria and identified structured passive surveillance of medical records. Univariate logistic regression was carried out to screen for potential risk factors, followed by multivariate analysis of selected variables. Among 376 mastectomy procedures performed in 306 dogs, 33 SSIs were detected, resulting in an overall incidence of 8.8% (95% CI: 6.1–12.1). The majority were superficial infections (93.9%), with only two cases classified as deep SSI; no organ/space infections were recorded. Prolonged anaesthesia duration (p = 0.041) and intraoperative hypothermia (p = 0.026) were independently associated with increased SSI risk. These findings indicate that the incidence of SSI after canine mastectomy is comparable to that reported for other clean surgeries. Prolonged anaesthesia and hypothermia represent modifiable risk factors, highlighting the importance of perioperative temperature control and optimized anaesthetic management. No significant associations were observed with patient-related variables, mastectomy type, or wound soaker catheter use, supporting its safe inclusion in multimodal analgesia.